The Rule of (The loss of the intended benefit from a thing is like the loss of the whole thing) (Rooting and practical) - Alzoubi, Ahmad Saad; Aljaber, Anas AbdElwahed (Journal of Islamic Sciences, 2022)
The study aims to define one of the rules for estimating the guarantee, which is: “the intended benefit will go from a thing, as the whole thing goes away، ” This rule is included in cases of estimating compensation for the guarantee in the case of infringement of money and bodies, and accordingly, the statement of the legal rulings entailed in the event of the loss of benefit from the thing Intended when estimating the guarantee, the research dealt with the concept of the rule with both detailed and total meanings, and a statement of the impact of the differing jurists in considering the financial benefit, and the most important jurisprudential applications on this rule were mentioned, and the researchers reached several results, the most prominent of which were: Notables and its missing, it guarantees that losing a thing is the same of the case of missing the whole thing.
Keywords: rules; benefit; The benefit is gone; the thing is gone; compensation